P64 Examination of genes encoding telomerase associated proteins suggests a prognostic relevance for NHP2 and NOP10 in endometrial cancer. (1st November 2019) - Button, L; Alnafakh, R; Drury, J; DeCruze, SB; Saretzki, G; Adishesh, M; Hapangama, D
Abstract : Introduction/Background: Risk of recurrence of endometrial cancer (EC) after surgical treatment is 13% and recurrent disease carries a poor prognosis. Research into prognostic indicators is essential to improve EC management and patient outcome. Cancer cell immortality is dependent on telomerase, but the role of telomerase-associated proteins is poorly understood. Protein encoding telomerase-associated genes such as NHP2 and NOP10 in the endometrium has not yet been described. Aims: To examine the prognostic association of genes encoding telomerase–associated proteins in EC in The Cancer Genome Atlas (TCGA) dataset. To characterise expression of the gene products with prognostic relevance in an independent sample set. Methodology: In silico study interrogated TCGA dataset; NHP2 and NOP10 were selected for further study in 20 healthy control and 19 EC samples. Proteins were detected using Western blotting; NHP2 co-expression with dyskerin (with known alteration in EC) was visualised using immunofluorescence and NHP2 immunohistochemical staining was semi-quantified using a quickscore. Results: Alterations in NHP2 and NOP10 RNA expression levels were associated with poor prognosis in EC; the respective proteins were detected for the first time in non-malignant premenopausal and postmenopausal endometrium as well as in EC in an independent patient cohort. Immunofluorescence demonstrates NHP2 co-expression with dyskerin in healthy and malignant endometrium, with an apparent loss of NHP2 and dyskerin in EC samples. A statistically significant decrease in NHP2 Quickscore was observed in EC relative to premenopausal ( p =0.0008) and postmenopausal ( p =0.01) samples. Conclusion: Our findings suggest a prognostic role for two telomerase-associated proteins NHP2 and NOP10 in EC. Further work is warranted to examine the functional role these proteins play in normal endometrial cellular proliferation as well as in EC. Disclosure: Nothing to disclose.